Comparing the mechanical energetics of walking among individuals with unilateral transfemoral limb loss using socket and osseointegrated prosthetic interfaces - Pawel R. Golyski; Benjamin K. Potter; Jonathan A. Forsberg; Brad D. Hendershot (Scientific Reports)
Abstract Osseointegration (OI), or bone-anchoring, of a prosthesis is a transformative procedure for addressing issues of socket fit among individuals with lower limb loss. Mechanically, the removal of the socket interface substantially alters the transmission of load and the flow of energy through the prosthetic limb. Here, we compared the mechanical energetics of walking between socket and OI interfaces using biomechanical data and custom models of 8 service members pre- and ~24-months post-OI. Relative to a socket interface, an OI interface shifted loads toward the intact limb, which increased collision losses, while the net mechanical work of both the prosthetic and intact limbs remained minimal for both interfaces. At the joint level, despite the removal of the socket interface potentially saving ~ 6 J of work per stride, these reduced collision losses were transmitted to the center of mass instead of altering joint work. The principal change in prosthetic limb joint mechanics with an OI interface was a decrease in negative prosthetic limb hip work during late stance, driven by a decreased hip flexion moment and prosthetic limb offloading. Our findings suggest that despite previously reported improvements in walking economy, after OI individuals likely walk with increased mechanical energetic asymmetry.